Identification of disrupted AUTS2 and EPHA6 genes by array painting in a patient carrying a de novo balanced translocation t(3;7) with intellectual disability and neurodevelopment disorder. (3rd September 2015) - Schneider, Anouck; Puechberty, Jacques; Ng, Bee Ling; Coubes, Christine; Gatinois, Vincent; Tournaire, Magali; Girard, Manon; Dumont, Bruno; Bouret, Pauline; Magnetto, Julia; Baghdadli, Amaria; Pellestor, Franck; et al.
Abstract : Intellectual disability (ID) is a frequent feature but is highly clinically and genetically heterogeneous. The establishment of the precise diagnosis in patients with ID is challenging due to this heterogeneity but crucial for genetic counseling and appropriate care for the patients. Among the etiologies of patients with ID, apparently balanced de novo rearrangements represent 0.6%. Several mechanisms explain the ID in patients with apparently balanced de novo rearrangement. Among them, disruption of a disease gene at the breakpoint, is frequently evoked. In this context, technologies recently developed are used to characterize precisely such chromosomal rearrangements. Here, we report the case of a boy with ID, facial features and autistic behavior who is carrying a de novo balanced reciprocal translocation t(3;7)(q11.2;q11.22)dn. Using microarray analysis, array painting (AP) technology combined with molecular study, we have identified the interruption of the autism susceptibility candidate 2 gene ( AUTS2 ) and EPH receptor A6 gene ( EPHA6 ). We consider that the disruption of AUTS2 explains the phenotype of the patient; the exact role of EPHA6 in human pathology is not well defined. Based on the observation of recurrent germinal and somatic translocations involving AUTS2 and the molecular environment content, we put forward the hypothesis that the likely chromosomal mechanism responsible for the translocation could be due either to replicative stress or to recombination‐based mechanisms. © 2015 Wiley Periodicals, Inc.